Hipertensão arterial sistêmica e fatores associados em população rural no Rio Grande do Sul - Raimundi, Jaqueline (2024)
Introduction: Systemic Arterial Hypertension is one of the Chronic Noncommunicable Diseases of important occurrence worldwide, representing one of the main risk factors for cardiovascular diseases, cerebrovascular and chronic kidney disease. The context of hypertension differs depending on conditions such as geographical location and socioeconomic factors. In rural areas, geographical barriers, the lack of health services, transport and cultural differences and lifestyles contribute to worse health conditions and the appearance of diseases such as hypertension. General Objective: To analyze the prevalence of self-reported systemic arterial hypertension in rural population and identify associated factors in a municipality in northern Rio Grande do Sul, Brazil. Specific Objectives: To estimate the prevalence of self-reported systemic arterial hypertension in rural population in Rio Grande do Sul; describe the sociodemographic characteristics and their relationship with Systemic Arterial Hypertension self-reported in rural population in Rio Grande do Sul; to analyze the health conditions of the rural population and its relationship with the Systemic Arterial Hypertension self-reported in Rio Grande do Sul; and its relationship with self-reported Systemic Arterial Hypertension in a rural population in Rio Grande do Sul.Methodology: A cross-sectional study, conducted in a northern gaucho municipality. The data collection took place from August to November 2023, through an interview with the application of a structured questionnaire containing sociodemographic characteristics, health, lifestyle and working conditions, aimed at the rural population living in the municipality of Seberi, Rio Grande do Sul, aged 18 years or more. Later the questionnaires were coded, The data were recorded in Excel and after transferred to the statistical software SPSS 22.0 The data were analyzed by descriptive and inferential statistics. Qualitative variables were tested by the chi-square test of Pearson and quantitative and qualitative variables by the exact test of Fisher. The associations in which p < 0.05, the estimated prevalence of systemic hypertension and their respective 95% confidence intervals (95%CI) were considered significant. The project was approved by a local research ethics committee. Results: The results were presented in a scientific article format, called "Systemic Arterial Hypertension and associated factors in rural population in Rio Grande do Sul". The study identified a prevalence of 57.1% of hypertension in the rural population, being more associated with female individuals (53.3%), self-declared white (93.9%) and age greater than or equal to 60 years (76.1%). Factors such as low education (82.6%) and income up to three minimum wages (88.7%). More than half of the hypertensive patients had blood pressure in the last thirty days (55.6%), presence of complications (27.7%) (PR=0.54; CI=0.47-0.62), comorbidities (48.0%) (PR=0.65; CI=0.54-0.77), use of continuous drugs (87.9%), antihypertensive (96.5%) (PR=0.23; CI=0.16-0.33 and PR=0.12; CI=0.06-0.27), attend health care service (PR=0.52; CI=0.35-0.76) showed as protective factors for hypertension and the use of pesticides as a risk factor (PR = 1.3; CI = 1.05-1.62). Conclusions: The research showed prevalence of Systemic Arterial Hypertension in more than half of the rural population, associating with factors such as advanced age, low education, which may lead to information difficulty resulting in the underdiagnosis of hypertension. The monitoring of treatment and health conditions of hypertensive patients is of great importance, especially by health services. Thus, the study will enable the elaboration of more specific prevention strategies, also collaborating for early diagnosis and better adherence and follow-up in the treatment of hypertension, by health teams.